Metode Analytic Hierarchy Process Untuk Mendukung Strategi Pengendalian Pencemaran Air Sungai Cokro Malang - Devita Sari; Tiwi Yuniastuti (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
The Cokro River is a tributary of the Amprong River whose river flows through several villages in Pakis District, Malang Regency, including Sumberpasir village and Pakiskembar village. Cokro River is located between residential areas and agricultural land and several industries. Industries in the Cokro river area are the leather industry, paper industry, and tofu factories. Anthropogenic activities result in river water pollution. The purpose of this study was to analyze the water quality and quality status of the Cokro River and to formulate a strategy to control water pollution in the Cokro River. This type of research is a mix method of qualitative and quantitative. Sampling was done by purposive sampling method, for pollution control strategies using the AHP method. The results of the water quality analysis show that the BOD and COD parameters exceed the class II and III quality standards at all points, the DO parameters are below the quality standard at points 3 and 5. The quality status at all points is lightly polluted on the quality criteria for class 2, while for class III quality criteria there is one point that is in good condition, that is point 4. AHP results show that the main priority is the social – institution aspect with the highest alternative solution value is to increase the role of the community in controlling river water pollution.